Females in higher education and leadership: insights from a multi-method approach - Correa, Alicia; Glas, Maria Gracia; Opara, Jana (Frontiers in Education, 2025)
Despite constituting more than half of higher education students globally, females remain underrepresented in academic roles, particularly in leadership positions that shape the future direction of higher education and impact society at large. This study, aligned with the UN’s Sustainable Development Goals 4 and 5, examines the gender gap in higher education and leadership across regional, national, and institutional contexts. Through descriptive analyses, surveys, and interviews, the research assesses female representation at various academic levels and identifies key factors influencing career progression. The findings reveal that gender parity in enrolment has been achieved, with Latin America & Caribbean leading, followed by Europe and Central Asia. However, parity in academic roles, such as teaching positions, remains unmet, with Central Asia showing higher female representation than Europe and Latin America & Caribbean. Parity in these roles is projected to be achieved well beyond 2030. Variations within regions, such as internal differences in Central Asia, emphasize the need for more granular analysis. Gender parity in senior and leadership roles is even further from being realized. Perceptions of obstacles faced by women in academia—such as work-life balance challenges and a lack of role models—are consistent across diverse regions and cultures. To address these issues, the results suggest improving visibility, offering mentoring programs, and promoting diverse leadership. Conducted across both developed and developing countries, the study concludes that achieving gender parity in leadership positions remains a distant goal, underscoring the need to reassess strategies to better align with the 2030 Agenda.